Resolving media disputes in defamation cases - Mohamed, Duryana; Mohd Badrol Afandi, Nor Hafizah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Media plays a very important role in the society. The society receive news and information through them and this explains why media related people such as the journalists, reporters, publishers and Internet Service Providers (ISP) must ensure they deliver correct news and information either through online or offline media. Nevertheless, sometimes people get false news and even certain reports can cause damage to certain people reputation and dignity. Generally, media is expected to comply with media and communication ethics. They should also know their rights and duties provided in the media and communication laws as well as other relevant laws. In Malaysia, the media especially the journalists are supposed to comply with the Code of Ethics for journalists and the ‘Rukunegara’which contains guidelines for them. However, in some cases the publishers and the reporters fail to comply with the media and communication ethics and the laws. As a result, people started to complain on false news and persons or companies affected will file the case against the publisher and the reporters. This is evidenced from various court decisions in Malaysia and some other countries. But medias also have their own defences based on the available laws such as Defamation Act 1957 (Malaysia) and other alternative method. Hence, this paper seeks to discuss the media rights and duties as well as defences available to them in resolving disputes particularly in defamation cases. Reference will include court cases and writings available online and offline.